The Influence of the Ammonolysis Temperature on the Photocatalytic Activity of β-TaON - Songhak Yoon; Alexandra E. Maegli; Santhosh Kumar Matam; Matthias Trottmann; Takashi Hisatomi; Céline Marie Leroy; Michael Grätzel; Simone Pokrant; Anke Weidenkaff (International Journal of Photoenergy)
Phase-pure tantalum oxynitride (β-TaON) powders were synthesized by thermal ammonolysis of Ta2O5 powders. X-ray diffraction revealed an enlargement of the unit cell and an increase of the crystallite size with increasing ammonolysis temperature. Scanning electron microscopy showed reduced particle sizes for β-TaON synthesized at 800 and compared to the precursor oxide. With increasing nitridation temperature the Brunauer-Emmett-Teller surface area was reduced and the nitrogen content increased. UV-Vis spectroscopy showed a bandgap energy of 2.6–2.4 eV. The highest oxygen evolution rate of 220 μmol·g−1·h−1 was achieved for β-TaON synthesized at . The factors determining the photocatalytic activity of β-TaON powders were found to be the specific surface area and defects in the β-TaON.